2020
DOI: 10.1371/journal.pone.0240167
|View full text |Cite
|
Sign up to set email alerts
|

A factor score reflecting cognitive functioning in patients from the Swiss Atrial Fibrillation Cohort Study (Swiss-AF)

Abstract: Background Atrial fibrillation (AF), the most common sustained cardiac arrhythmia, is considered as risk factor for the development of mild cognitive impairment (MCI) and dementia. However, dynamics of cognitive functions are subtle, and neurocognitive assessments largely differ in detecting these changes. We aimed to develop and evaluate a score which represents the common aspects of the cognitive functions measured by validated tests (i.e., "general cognitive construct"), while reducing overlap between tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…We also used the Swiss-AF Cognitive Construct (CoCo) score for cognitive assessment. 12 The CoCo score is composed of 17 differently weighted combined items from all the above-mentioned individual neuro-cognitive tests. It is a factor score developed for the Swiss-AF study allowing for the quantification of cognitive function and accounting for variance in all items from the full test battery.…”
Section: Methodsmentioning
confidence: 99%
“…We also used the Swiss-AF Cognitive Construct (CoCo) score for cognitive assessment. 12 The CoCo score is composed of 17 differently weighted combined items from all the above-mentioned individual neuro-cognitive tests. It is a factor score developed for the Swiss-AF study allowing for the quantification of cognitive function and accounting for variance in all items from the full test battery.…”
Section: Methodsmentioning
confidence: 99%
“…Next to executive functioning and processing speed, the difference between AF subgroups was also present in the cognitive construct (CoCo) score ( 19 ). It has previously been shown that the CoCo score is likely to be more granular and more sensitive to detect small changes in cognitive function ( 19 ) which may be missed when examining each neurocognitive test alone ( 12 , 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…The cognitive test battery consisted of five validated, widely used cognitive tests administered at each follow-up. The test battery included the Montreal Cognitive Assessment (MoCA) ( 22 ), Trail Making Test Part A (TMT-A) ( 23 , 24 ) Trail Making Test Part B (TMT-B) (TMT results calculated as number of correct connections per second) ( 23 , 24 ), Semantic Fluency test (SF) ( 25 ) and the Digit Symbol Substitution Test (DSST) ( 26 , 27 ), described in detail elsewhere ( 19 ). All cognitive tests were administered in a paper-pencil format or, during the coronavirus disease 2019 (COVID-19) pandemic, in part (i.e., MoCA and SF) by telephone.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Digit Symbol Substitution Test (DSST) explores cognitive aspects such as information processing speed, visuomotor coordination, and attention [19]. The cognitive construct (CoCo) score is a score previously derived from the individual components of all neurocognitive tests performed in Swiss-AF (MoCA, TMT, SFT, DSST) using latent factor analysis and summarizes global cognitive performance [29].…”
Section: Neurocognitive Functionmentioning
confidence: 99%